COMPARISON OF EFFECTS OF ABDOMINAL STRETCHING EXERCISE AND COLD COMPRESS THERAPY ON MENSTRUAL PAIN INTENSITY IN TEENAGE GIRLS - Desta Ayu Cahya Rosyida; Agus Suwandono; Ida Ariyanti; Suhartono Suhartono; Imam Djamaluddin Mashoedi; Diyah Fatmasari (Belitung Raya Foundation, Indonesia, 2017)
Background: Pain during menstruation is not uncommon, especially in young women, which has an impact on their life activities. Objective: To examine the effect of abdominal stretching exercise and cold compress therapy on decreasing intensity of menstrual pain in teenage girls. Design: A quasi-experimental study with two group comparison pretest-posttest design at SMK Bakti Indonesia Medika, Indonesia. There were 46 respondents selected in this study by consecutive sampling that consisted of 23 samples in the abdominal stretching exercise group and 23 samples in the cold compress group. The menstrual pain was measured using VAS (visual analog scale). Data were analyzed using Mann-Whitney, Chi-Square, and Wilcoxon test. Results: Findings showed that the mean of menstrual pain before intervention in the abdominal stretching exercise was 7.04 and in the cold compress therapy was 6.74 with p-value 0.211 (<0.05), which indicated that there was no mean difference of pain between both groups. However, after intervention, the menstrual pain was reduced from 7.04 to 1.91 (5.09 difference) in the abdominal stretching exercise group; and from 6.74 to 5.52 (1.22 difference) in the cold compress group with p-value 0.000 (<0.05), which indicated that there was statistically significant difference of menstrual pain before and after intervention, both abdominal stretching exercise and cold compress therapy. Conclusion: There were statistically significant effects of abdominal stretching exercise and cold compress therapy on menstrual pain in teenage girls. The abdominal stretching exercise is more effective than cold compress therapy in reducing menstrual pain intensity. Thus, it is suggested that abdominal stretching exercise can be an alternative choice of management of dysmenorrhea in teenage girls, and can be a part of subject in the education as non-pharmacological medicine.